Farm size and biosecurity measures associated with Strongylus vulgaris infection in horses - Hedberg Alm, Ylva; Tydén, Eva; Martin, Frida; Lernå, Jessica; Halvarsson, Peter (Swedish University of Agricultural Sciences, 2024)
The dataset contains raw data from a survey study aimed at investigating the incidence and risk factors associated with large bloodworm infection. The data also contains a file with the zip code of where the respondent lives and the GPS coordinates of the zip code. The postal code data has been separated from the other data and has been processed separately from the survey's raw data.

Datamaterialet innehåller rådata från en enkätstudie som syftar till att undersöka förekomst och riskfaktorer assoccierade med infektion av stora blodmasken. Datat innehåller också en en fil med postnummer över var den svarande bor samt postnumrets GPS-koordinater. Postnummerdatat har separerats från övriga data och har behandlats separat från enkätens rådata.
Gårdsstorlek och biosäkerhetsåtgärder associerade med Strongylus vulgaris-infektion hos hästar
Keywords: Administrative units; Administrativa enheter; Coordinate reference systems; Referenskoordinatsystem; horse stables; häststall; questionnaire survey; enkätundersökning; Stongylus vulgaris; Stor blodmask; Plants and animals; Växter och djur; Biological Sciences; Biologi; Veterinary Science; Veterinärmedicin; Biota; Biologi och ekologi